Fikih sebagai pedoman hidup: Menjaga integritas moral dalam menghadapi perubahan sosial - Nafi’a, Moh. Zidni Ilman (Maliki Interdisciplinary Journal, 2024)
The role of jurisprudence in maintaining adolescent morals is as a science that must be studied by adolescents. Adolescence is an important period in human development. At this time, teenagers begin to search for their identity and build their moral foundations. In the era of modernization and various external influences, fiqh trying to maintain adolescent morality has become a crucial challenge. Through fiqh tools, humans know which actions are good and which actions are bad. Fiqh is a set of rules for improving a person's morality both towards His Lord and towards fellow humans. Fiqh provides clear guidance and direction for teenagers in living their lives. Fiqh teachings instill noble moral values. These values can help teenagers to differentiate between good and bad.